Analisys of round wood production and profit sharing of Shorea leprosula and Shorea smithiana at PT Inhutani I Bukit Bangkirai Balikpapan - Moises Soares; Abubakar M Lahjie; BDAS Simarangkir; Yosep Ruslim (Universitas 17 Agustus 1945 Samarinda, 2019)
This study investigated the roundwood production and profit sharing for Shorea leprosula and Shorea smithiana in case of PT Inhutani I Bukit Bangkirai, Balikpapan. Five research aims pursued in order to better understand the economic valuation of Shorea tree species, are: 1) analyse the increments of woody; 2) identify the age of trees reached the highest increments of woody; 3) measure the highest value of mean annual increments (MAI); 4) examine the nominal rate of return (i) for roundwood production; 5) examine the profit sharing between the management of PT Inhutani I Bukit Bangkirai and investors. Additionally, the policy of profit sharing has been determined by the proportion of 55% for investors and 45% for the management.The results demonstrated that: 1) the wood potential of Shorea leprosula reached the highest value at the age of 40 years by producing 7.78 m3 ha-1 year-1, and Shorea smithiana reached the highest value at the age of 50 years by producing 333.34 m3 ha-1 year-1; 2) the highest value of MAI for Shorea leprosula and Shorea smithiana are 7.78 and 6.67 m3 ha-1 year-1 respectively; 3) the nominal rate of return (i) of Shorea leprosula is 7.8% for investors and 8.3% for the management, and Shorea smithiana is 6.3% for investors and 6.7% the management. Overall, this research found that the economic value of Shorea leprosula and Shorea smithiana provide the nominal rate of return (i), which is higher than minimum acceptable rate of return (MAR).